The Process of being a Teacher in a Reggio Emilia-Inspired Preschool: A Phenomenological Study - Tugba AYDEMIR OZALP; Hatice Zeynep INAN (Anı Publishing, 2021)
The current research aims to examine how Reggio Emilia-inspired preschool teachers in Turkey make sense of being Reggio Emilia-inspired teacher and what they experience during this process. In this research, one of the qualitative research methods, namely, Phenomenological Research Design, was used. Data were collected using semi-structured interviews. In this study, 20 preschool teachers in Reggio Emilia-inspired schools located in Istanbul, Ankara, and Izmir provinces were included. Participants were determined using the purposeful sampling strategy. For data analysis, this research was conducted using the thematic analysis in which categories and codes were created upon similarities found in the data. The findings obtained in this study revealed that a teacher who was inspired by the Reggio Emilia Approach experiences five stages of transformation. These stages were as follows, respectively: 1. Hearing the Reggio Emilia approach for the first time, 2. Affective reaction 3. Internalization 4. Comparison 5. Placement. Participants in the current research stated that being a Reggio Emilia-inspired teacher was a pleasant, enjoyable, intensive process and an endless journey in which they helped children construct their knowledge.